Sugar ester synthesis by thermostable lipase from Streptomyces thermocarboxydus ME168 - H-Kittikun A. (2014)
The extracellular lipase from Streptomyces thermocarboxydus ME168 was purified to 9.5-fold with 20% yield, following concentration by acetone precipitation, ion exchange chromatography (Resource Q) and gel filtration chromatography (Superdex 200), respectively. The purified enzyme had an apparent molecular mass of 21 kDa by sodium dodecyl sulphate polyacrylamide gel electrophoresis (SDS-PAGE). The N-terminal sequence of the lipase was ASDFDDQILG and was different from most other reported lipase. The enzyme showed maximum activity at 50 °C with the half-life of 180 min at 65 °C. It showed high stability at a broad pH range of 5.5-9.5 and was thermostable at the temperature range of 25-60 °C. The K m and V max were 0.28 mM and 1,428 U/mg, respectively, using p-nitrophenyl palmitate as substrate. It was active toward p-nitrophenyl ester with medium to long acyl chain (C 8-C 16). Lipase activity was inhibited by Zn 2+, dithiothreitol (DTT), EDTA and some organic solvents, e.g., ethanol, acetone, dioxane, acetronitrile, tertbutanol and pyridine. Immobilized crude lipase of S. thermocarboxydus ME168 on celite could be used to synthesize sugar esters from glucose and vinyl acetate, vinyl butyrate or vinyl caproate in tert-butanol:pyridine (55:45 v/v) at 45 °C with conversion yields of 93, 67 and 55%, respectively. © Springer Science+Business Media, LLC 2012.